2014
DOI: 10.4062/biomolther.2013.102
|View full text |Cite
|
Sign up to set email alerts
|

α-Asarone Ameliorates Memory Deficit in Lipopolysaccharide-Treated Mice via Suppression of Pro-Inflammatory Cytokines and Microglial Activation

Abstract: α-Asarone exhibits a number of pharmacological actions including neuroprotective, anti-oxidative, anticonvulsive, and cognitive enhancing action. The present study investigated the effects of α-asarone on pro-inflammatory cytokines mRNA, microglial activation, and neuronal damage in the hippocampus and on learning and memory deficits in systemic lipopolysaccharide (LPS)-treated C57BL/6 mice. Varying doses of α-asarone was orally administered (7.5, 15, or 30 mg/kg) once a day for 3 days before the LPS (3 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 42 publications
3
49
0
1
Order By: Relevance
“…Apart from its traditional claims, scientific reports showed that AGR can be used as neuroprotective (Jiang et al, 2012;Limon et al, 2009;Manikandan and Devi, , anticonvulsant (Pages et al, 2010) and hyperlipidemic agent (Garduno et al, 1997). Recent evidence showed that a-asarone ameliorated memory deficits in LPS-treated mice via its antiinflammatory actions (Shin et al, 2014). However, the effects of the active constituent α-asarone isolated from AGR in PDrelated neuroinflammatory conditions and the intrinsic mechanisms involved in regulating microglia-mediated signaling pathways were not documented.…”
Section: Introductionmentioning
confidence: 97%
“…Apart from its traditional claims, scientific reports showed that AGR can be used as neuroprotective (Jiang et al, 2012;Limon et al, 2009;Manikandan and Devi, , anticonvulsant (Pages et al, 2010) and hyperlipidemic agent (Garduno et al, 1997). Recent evidence showed that a-asarone ameliorated memory deficits in LPS-treated mice via its antiinflammatory actions (Shin et al, 2014). However, the effects of the active constituent α-asarone isolated from AGR in PDrelated neuroinflammatory conditions and the intrinsic mechanisms involved in regulating microglia-mediated signaling pathways were not documented.…”
Section: Introductionmentioning
confidence: 97%
“…Antibody specificity for IL-1β was confirmed by preabsorption with recombinant mouse IL-1β, which blocked further staining with the IL-1β antibody. This antibody has been previously used for immunohistochemistry in mouse 38,39 and detects both the inactive, precursor and active form of IL-1β 40 . The Iba-1 antibody 41,42 and NeuN antibody 43,44 have been extensively used in mice.…”
Section: Methodsmentioning
confidence: 99%
“…Compelling evidence demonstrates that compounds such as alpha-tocopherol, edaravone, alpha-asarone having antioxidant properties can reduce neuroinflammation and neuronal degeneration in various models of epilepsy (Betti et al, 2011;Miyamoto et al, 2008;Shin et al, 2014). Curcumin (diferuloyl methane) is a polyphenolic diketone found in Curcuma longa Linn.…”
Section: Introductionmentioning
confidence: 97%